Study of AlSi7Mg0.6 Alloy by Selective Laser Melting: Mechanical Properties, Microstructure, Heat Treatment - Mauduit, Arnold; Gransac, Hervé; Auguste, Pierre; Pillot, Sébastien (Journal of Casting & Materials Engineering, 2019)
This study presents a panorama of the AlSi7Mg0.6 (A357) aluminum alloy in additive manufacturing by selective laser melting. The document is mainly interested in the metallurgical tempers obtained after manufacture and after heat treatment; it quickly cover the process. The results concerning the material integrity (porosity), mechanical properties, microstructures, residual stresses, etc., are presented in order to best define the technological capacities of these metallurgical tempers: as-built, soft annealed, T6, and artificial aging. Some information on the mechanisms and kinetics of precipitation is also presented using the Johnson–Mehl–Avrami–Kolmogorov model. Finally, the conclusion proposes an inventory (advantages/disadvantages) of the metallurgical tempers obtained to better understand the industrial applications.